Experimental investigation of a residential multi-split air-conditioning system with partial heat recovery for domestic hot water - Yujue Zhou; Baolong Wang; Wenxing Shi; Zhigang Wang; Qingfeng Bie; Xianguo Jiang; Zhanwen Zhao (Energy and Buildings, 2026)

Lymph node-targeted H2S-self-releasing multifunctional prodrug for the dual remodeling of immunological and redox homeostasis in autoimmune uveitis - Qinjin Dai; Yuelan Wu; Wenbo Geng; Mengna Li; Wanyun Zhang; Yuxian Lai; Pei Zhang; Xiaoyue Zhang; Chunjiang Zhou; Yinuo Wang; Qingfeng Cao; Xiang Luo; et al. (Chemical Engineering Journal, 2026)

Spatial and temporal evolution of the groundwater depth and indirect effects during the spring irrigation period in the Hetao Irrigation District - Yi Zhao; Haibin Shi; Xianyue Li; Shuya Yang; Haoqi Han; Yunlei Dong; Qingfeng Miao; Jianwen Yan; Cong Hou; Xu Dou (Irrigation Science, 2026)

Optimization of fertilization regimes for major crops in the Hetao Irrigation District based on the DNDC model and evaluation of economic benefits - Cong Hou; Haibin Shi; Yan Yan; Qingfeng Miao; Yi Zhao; Sihan Xue; Jiapeng Zhang; Weiping Li (European Journal of Agronomy, 2026)

Defect-mediated rigid-flexible coupled architecture for upcycling of spent O3-type sodium-ion cathodes - Qingfeng Liu; Jinhua Shi; Fanbin Hu; Zitong Fei; Yun Shen; Haigang Dong; Qi Meng; Peng Dong; Yingjie Zhang (Chemical Engineering Journal, 2026)

High-performance, durable bamboo conductive macrofibers based triboelectric nanogenerator for stable harvesting water wave energy - Jiaqi Liao; Qingyu Meng; Wenwen Zhu; Wenhao Xu; Yang Peng; Shitao Shi; Zewei Ye; Chencong Liu; Qingfeng Sun; Xiaoping Shen (Chemical Engineering Journal, 2026)

Seasonal characteristics of atmospheric oxidizing capacity at environmental background area in North China from long-term field observations of O3, HONO and HCHO - Shuangshuang Ge; Zhiqiang Ma; Hailiang Zhang; Hanyu Zhang; Weiwei Pu; Yulu Qiu; Jinlong Hou; Chao Liu; Yucong Guo; Fan Dong; Di He; Liyan Zhou; et al. (Atmospheric Environment, 2026)

Electronic structure reconstruction and interface anchoring for high-performance direct regeneration of spent LiFePO4 materials - Yuyun Li; Yuan Ping; Fanbin Hu; Changjiang Li; Jinhua Shi; Haigang Dong; Qingfeng Liu; Yingjie Zhang; Qi Meng; Peng Dong (Chemical Engineering Journal, 2026)

Two-phase structure optimization of Al-doped Ag1.995Te0.5S0.5 for improved mechanical and thermoelectric properties - Min Zhu; Xiao-Lei Shi; Hao Wu; Meng Li; Wei-Di Liu; De-Zhuang Wang; Liang-Cao Yin; Wen-Yi Chen; Yan Huang; Zhi-Gang Chen; Qingfeng Liu (Chemical Engineering Journal, 2026)

Cost-minimizing alternative dosage regimens of imipenem/cilastatin/relebactam for patients with renal impairment: a pharmacokinetic/pharmacodynamic simulation study - Xiaoping Shi; Donghui Lao; Qing Xu; Xiaoyu Li; Bijue Liu; Qingfeng He; Xiao Zhu; Qianzhou Lv (European Journal of Clinical Pharmacology, 2026)

Macro‐Hybrid and Micro‐Hybrid of Fish - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
This study reviews the progress in fish breeding, focusing on distant hybridization and gynogenesis, and introduces the theory of macro‐hybrid and micro‐hybrid. The macro‐hybrid refers to the allo‐progeny derived from distant hybridization, including the allo‐progenies. The micro‐hybrid refers to the auto‐progenies derived from distant hybridization or heterologous sperm‐induced gynogenesis, which possess a genome derived predominantly from the maternal but contain DNA fragments originating from the paternal. Macro‐hybrids induce significant phenotypic changes, while micro‐hybrids improve growth rate and stress resistance. Both hybridization and gynogenesis exhibit high selective pressure. This review elucidates how selective pressures (homozygosity + heterologous sperm + cold/heat shock) of the heterologous sperm‐induced gynogenesis contribute to the generation of effective genetic variations. The study also presents the technologies of macro‐hybrid and micro‐hybrid. In macro‐hybrids of distant hybridization, parental chromosome numbers are closely matched, enabling the formation of fertile allo‐diploid and allo‐tetraploid strains. In micro‐hybrid of distant hybridization, equal or differing chromosome numbers between parents yield fertile auto‐tetraploid and auto‐diploid strains. In micro‐hybrid of heterologous sperm‐induced gynogenesis, equal or different chromosome numbers between parents yield auto‐diploid strains. The integration of heterologous sperm‐induced gynogenesis, back‐cross, and self‐cross strategies can address the issue of all‐female progeny resulting from gynogenesis. A series of auxiliary breeding techniques is established to support the macro‐hybrid and micro‐hybrid breeding. Case studies of superior fish strains developed through macro‐hybrid and micro‐hybrid breeding are presented. The establishment of macro‐hybrid and micro‐hybrid theory and breeding technologies holds significant value for fish breeding.

Cover Image - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
The cover image is based on the article Macro‐Hybrid and Micro‐Hybrid of Fish by Shaojun Liu et al., https://doi.org/10.1111/raq.70106 . image

A carbon-negative aerogel with superior CO₂ capture, flame retardancy, and strength based on a cellulose/MOF three-dimensional network - Huinan Wang; Lingling Zhu; Wenjie Xia; Mingdi Kang; Qianqian Zhou; Weichen Shi; Xinyi Xiang; Qingfeng Sun; Yingying Li (Chemical Engineering Journal, 2025)

SuFEx-derived macrocyclic polysulfates for efficient dual capture of methyl iodide and iodine - Shuai Shi; Zhonglin Ma; Long Chen; Yuqi Zhang; Haibin Shi; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2025)

Multifunctional hydrogel-modified laminated wood for high-strength and fire-resistant structural applications - Zewei Ye; Haomeng Yu; Wenwen Zhu; Shitao Shi; Jiaqi Liao; Chencong Liu; Qingfeng Sun; Xiaoping Shen (Chemical Engineering Journal, 2025)

Ultrasound triggered spatial-temporal NO gas release to enhance sonodynamic therapy and immune checkpoint blockade therapy against pancreatic cancer - Wanrui Shi; Jianfeng Zhang; Ruiqi Wu; Shiti Shama; Shi Tan; Heng Xue; Yan Sun; Qingshuang Tang; Suhui Sun; Rui Tang; Guotao Feng; Xiaoda Li; et al. (Chemical Engineering Journal, 2025)

Review of biological algal fertilizer technology: Alleviating salinization, sequestering carbon, and improving crop productivity - Siyao Dai; Weiying Feng; Fanhao Song; Tingting Li; Yingru Tao; Fang Yang; Qingfeng Miao; Pengcheng Duan; Haiqing Liao; Haibin Shi; José Manuel Gonçalves; Isabel Maria Duarte (Bioresource Technology, 2025)

Reduced serum levels of mitochondria-derived peptide MOTS-c in patients with obstructive sleep apnea - Zhuoding Luo; Rui Ji; Renjing Ye; Yawen Shi; Qingfeng Pang; Min Yin (Sleep and Biological Rhythms, 2025)

Evaluation of slag and tannery sludge based geopolymer after thermal exposure: Properties, phase transformation and Cr leaching behavior - Jialin Chen; Jingfei Zhou; Shoukai Chen; Haibo Shi; Qingfeng Hu; Yingdong Tang (Journal of Cleaner Production, 2025)

Mechanistic model for the cotransport of colloids and radionuclides in saturated porous systems based on the interaction forces between colloids - Qi Tan; Qingfeng Tang; Xinyi Shi; Hongjie Zhao; Shuyang Li; Yuan Chen; Xiaoyan Wei; Zhen Xu; Duoqiang Pan; Wangsuo Wu (Applied Geochemistry, 2025)

Different ploidy-level hybrids derived from female common carp × male topmouth culter - Conghui Yang; Chenghua Dai; Qiong Liu; Yating Zhu; Xuexue Huang; Xiaowei Xu; Yi Zhou; Shi Wang; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

Water and land use in China's food systems: Exploring potential mitigation strategies - Wenjun Shi; Hanlin Liu; Yosef Steinberger; Yuanchao Hu; Yang Yang; Qingfeng Meng; Guanghui Xie (Sustainable Production and Consumption, 2025)

Incorporating graphene quantum dots boosts thermoelectric performance of PEDOT:PSS films - Ting Wu; Xiao-Lei Shi; Yu-Yu Deng; Yuan-Meng Liu; Min Zhu; Wei-Di Liu; Meng Li; Fang Yue; Pei Huang; Zhi-Gang Chen; Qingfeng Liu (Chemical Engineering Journal, 2025)

The Research Advances in Distant Hybridization and Gynogenesis in Fish - Qizhi Liu; Shi Wang; Chenchen Tang; Min Tao; Chun Zhang; Yi Zhou; Qinbo Qin; Kaikun Luo; Chang Wu; Fangzhou Hu; Yude Wang; Qingfeng Liu; et al. (Reviews in Aquaculture, 2025)
Distant hybridization and gynogenesis are two prevalent breeding techniques for fishes. Drawing from the research achievements of our team and the existing literature, we summarize the reproductive traits and genetic features of fishes derived from distant hybridizations and gynogenesis, and we deduce the fundamental mechanisms of these two methods and compare them, discerning their common and different characteristics. Both distant hybridization and gynogenesis techniques can alter genotypes and phenotypes, thus establishing them as significant breeding methods. Additionally, the genetic principles and the basic biological characteristics of distant hybridization and gynogenesis in fish have been inferred. We propose the concepts of macro‐hybrid and micro‐hybrid based on extensive experimental findings from fish distant hybridizations and gynogenesis. The term “macro‐hybrid” refers to offspring from distant hybridization that possess two distinct subgenomes, each inherited from one of the two parental species, such as allodiploid and allotetraploid lineages. The concept of “micro‐hybrid” refers to offspring, including autodiploid and autotetraploid lineages, as well as those resulting from artificial gynogenesis, whose genome almost originates solely from the maternal parent but in which certain DNA fragments derived from the paternal parent insert. Distant hybridization and gynogenesis are vital techniques in fish genetics, breeding, and evolution. We highlight the prospective paths for research and application of distant hybridization and gynogenesis in fishes.

High-performance thermoelectric PEDOT:PSS fiber bundles via rational ionic liquid treatment - Yu-Yu Deng; Xiao-Lei Shi; Ting Wu; Hao Wu; Yuan-Meng Liu; Min Zhu; Wei-Di Liu; Meng Li; Pei Huang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Gckr depletion leads to growth retardation and diet-dependent visceral obesity in red crucian carp (Carassius auratus red var.) - Juan Li; Huilin Li; Yuan Ou; Qiyong Lou; Zehong Wei; Ming Wen; Shi Wang; Qingfeng Liu; Yuqin Shu; Shaojun Liu (Aquaculture, 2024)

Spatial and temporal heterogeneity of soil salinity and ionic coupling relationship under the water-saving renovation of a typical irrigation district in arid and semi-arid areas - Shuya Yang; Qingfeng Miao; Haibin Shi; Yi Zhao; Xiaoyu Liu; Xin Nie; Weiying Feng; José Manuel Gonçalves; Tao Zhang; Yuxin Li; Yuli Luo (Science of The Total Environment, 2024)

Predicting anion diffusion in bentonite using hybrid machine learning model and correlation of physical quantities - Tao Wu; Junlei Tian; Xiaoqiong Shi; Zhilong Li; Jiaxing Feng; Zhengye Feng; Qingfeng Li (Science of The Total Environment, 2024)

Engineering SuFEx-derived macrocyclic polysulfates for superior dynamic iodine capture at high temperatures - Shuai Shi; Zhonglin Ma; Haibo Wan; Long Chen; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2024)

Optimising microbial processes with nano-carbon/selenite materials: An eco-friendly approach for antibiotic resistance mitigation in broiler manure - Lizhi Li; Weikun Guan; Baohua Xiao; Qin He; Gangfu Chen; Jianzhong Wu; Zhigang Zhao; Feng You; Jinsheng Yang; Yue Xing; Lijun Zhou; Jinmeng Shi; et al. (Chemical Engineering Journal, 2024)

Global Trends and Networks in Soil Fertility Enhancement Techniques: a Bibliometric Analysis - Zhuangzhuang Feng; Qingfeng Miao; Haibin Shi; Xianyue Li; Jianwen Yan; José Manuel Gonçalves; Dandan Yu; Yan Yan; Weiying Feng (Journal of Soil Science and Plant Nutrition, 2024)

Effects of ambient temperature and humidity on COPD mortality in Ganzhou city, China - Chenyang Shi; Jinyun Zhu; Qingfeng Wu; Yanhong Liu; Yanbin Hao (International Journal of Biometeorology, 2024)

Irrigation scheduling in sand-layered farmland: Evaluation of water and salinity dynamics in the soil by SALTMED-1D model under mulched maize production in Hetao Irrigation District, China - Zhuangzhuang Feng; Qingfeng Miao; Haibin Shi; Xianyue Li; Jianwen Yan; José Manuel Gonçalves; Liping Dai; Weiying Feng (European Journal of Agronomy, 2024)

Effect of advance rate on excess pore water pressure induced by TBM tunnelling in saturated sand - Qingfeng Shi; Tao Xu; Dingwen Zhang (Computers and Geotechnics, 2024)

Acid doped branched poly(biphenyl pyridine) membranes for high temperature proton exchange membrane fuel cells and vanadium redox flow batteries - Ning Shi; Guorui Wang; Qian Wang; Lele Wang; Qingfeng Li; Jingshuai Yang (Chemical Engineering Journal, 2024)

A biomass-enhanced bentonite slurry for shield tunnelling in the highly permeable soil - Tao Xu; Xiaoyu Wu; Jiaxin Liu; Qingfeng Shi; Jinquan Shi (Tunnelling and Underground Space Technology, 2024)

Vertically designed high-performance and flexible thermoelectric generator based on optimized PEDOT:PSS/SWCNTs composite films - Binjie Xia; Xiao-Lei Shi; Li Zhang; Jia Luo; Wen-Yi Chen; Boxuan Hu; Tianyi Cao; Ting Wu; Wei-Di Liu; Yanling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Identification of sex locus and a male-specific marker in blunt-snout bream (Megalobrama amblycephala) using a whole genome resequencing method - Ming Wen; Siyu Wang; Chunchun Zhu; Yuxin Zhang; Zheng Liu; Chang Wu; Shi Wang; Yude Wang; Li Ren; Min Tao; QinBo Qin; Chun Zhang; et al. (Aquaculture, 2024)

LncFASA promotes cancer ferroptosis via modulating PRDX1 phase separation - Xiao Fan; Fangzhou Liu; Xiang Wang; Ying Wang; Yu Chen; Chengyu Shi; Xinwan Su; Manman Tan; Qingfeng Yan; Jinrong Peng; Jianzhong Shao; Yan Xiong; et al. (Science China Life Sciences, 2024)

Potential of novel zinc-based nanomaterials on the microbial community, antibiotic resistance genes, and DNA replication in animal manure - Haibo Zhang; Lizhi Li; Gangfu Chen; Nancheng Yin; Jiangao Guo; Xinrui Ni; Yixin Liu; Ke Wu; Weikun Guan; Cheng Zhang; Xiaochun Wu; Shi Wenkai; et al. (Chemical Engineering Journal, 2024)

Insight into Impact of Phosphate on the Cotransport and Corelease of Eu(III) with Bentonite Colloids in Saturated Quartz Columns - Qingfeng Tang; Zhen Xu; Qi Tan; Xingyi Shi; Wangsuo Wu; Duoqiang Pan (Journal of Hazardous Materials, 2024)

Lignocellulose/chitosan hybrid aerogel composited with fluorescence molecular probe for simultaneous adsorption and detection of heavy metal pollutants - Congcong An; Ming Zhang; Zhihao Xiao; Qingfeng Yang; Lijuan Feng; Siying Li; Meihui Shi (Journal of Environmental Chemical Engineering, 2023)

Theoretical investigation of outer-sphere adsorption of hydrated yttrium ion on the basal surfaces of kaolinite: A density functional study - Bing Li; Xuefa Shi; Chuanshun Li; Qingfeng Hua; Xinfang Li; Quanshu Yan (Chemical Geology, 2023)

Advances in Ag2S-based thermoelectrics for wearable electronics: Progress and perspective - Min Zhu; Xiao-Lei Shi; Hao Wu; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2023)

Spatial pattern and cause of centennial-scale hydroclimatic variability over eastern China during the last millennium - Jian-Jun Yin; Zhijun Wang; Wenqiang Shi; Qingfeng Shao; Xia Wu; Wei Tang; Yuan Ma (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Advances in Ag2S-based thermoelectrics for wearable electronics: progress and perspective - Min Zhu; Xiao-Lei Shi; Hao Wu; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2023)

Variation in Sunshine Duration and Related Aerosol Influences at Shangdianzi GAW Station, China: 1958–2021 - Weijun Quan; Zhiqiang Ma; Ziming Li; Xiaolan Li; Yingruo Li; Xiangao Xia; Huaigang Zhou; Hujia Zhao; Zhenfa Wang; Weiwei Pu; Fan Dong; Di He; et al. (Journal of Meteorological Research, 2023)

Experimental Study on the Influence of Temperature on Rock Salt Creep - Zhikai Dong; Yinping Li; Haoran Li; Ziheng Wang; Xilin Shi; Xiangsheng Chen; Qingfeng Lu (Rock Mechanics and Rock Engineering, 2023)

Anti-swellable cellulose hydrogel for underwater sensing - Zhuyue Lan; Yuanyuan Wang; Ke Hu; Shitao Shi; Qingyu Meng; Qingfeng Sun; Xiaoping Shen (Carbohydrate Polymers, 2023)

New remains of Ailuropoda melanoleuca baconi from Yanjinggou, China: Throwing light on the evolution of giant pandas during the Pleistocene - Haiqian Hu; Haowen Tong; Qingfeng Shao; Guangbiao Wei; Haidong Yu; Jingsong Shi; Xunqian Wang; Can Xiong; Yu Lin; Ning Li; Zhaoying Wei; Ping Wang; et al. (Journal of Mammalian Evolution, 2023)

SWCNTs/Ag2Se film with superior bending resistance and enhanced thermoelectric performance via in situ compositing - Qin-Xue Hu; Wei-Di Liu; Li Zhang; Wei Sun; Han Gao; Xiao-Lei Shi; Yan-Ling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2023)

Simultaneous promotion of mechanical and electrical properties of hot-pressing halloysite-based mullite ceramics through carbon incorporation - He Zhang; Liangcao Yin; Qingfeng Liu; Yazhong Chen; Shi Jin; Kesong Xiao; Huanyu Zhu; Xianlong Zhang; Xueping Wu (Applied Clay Science, 2023)

Development of a recombinant adenovirus-vectored vaccine against both infectious hematopoietic necrosis virus and infectious pancreatic necrosis virus in rainbow trout (Oncorhynchus mykiss) - Shouhu Li; Xincang Li; Rui Yuan; Xiaoxue Chen; Shouxu Chen; Yu Qiu; Qingfeng Yang; Meng Wang; Jiangao Shi; Shuo Zhang (Fish & Shellfish Immunology, 2023)

Association between environmental phenols and all-cause and cancer mortality - Jing He; Qingfeng Xue; Xin Hua; Quanqing Li; Ziwei Chen; Cindy Zhu; Wenyu Shi (Environmental Science and Pollution Research, 2022)

An improved hybrid bream derived from a hybrid lineage of Megalobrama amblycephala (♀)×Culter alburnus (♂) - Dingbin Gong; Min Tao; Lihui Xu; Fangzhou Hu; Zehong Wei; Shi Wang; Yude Wang; Qingfeng Liu; Chang Wu; Kaikun Luo; Chenchen Tang; Rong Zhou; et al. (Science China Life Sciences, 2022)

TEAD4 overexpression suppresses thyroid cancer progression and metastasis in vitro by modulating Wnt signaling - Buyong Zhang; Qingqing Wang; Yanting Ji; Xuan Zhang; Lingbo Xue; Qingfeng Shi; Jie Li (Journal of Biosciences, 2022)

Chelerythrine Ameliorates Pulmonary Fibrosis via Activating the Nrf2/ARE Signaling Pathway - Ling Peng; Li Wen; Qingfeng Shi; Feng Gao; Bin Huang; Changming Wang (Cell Biochemistry and Biophysics, 2021)

Distinct methylome patterns contribute to ecotypic differentiation in the growth of the storage organ of a flowering plant (sacred lotus) - Hui Li; Xingyu Yang; Qingfeng Wang; Jinming Chen; Tao Shi (Molecular Ecology, 2021)
DNA methylation is an epigenetic modification involved in phenotypic diversity, plant development, and environmental responses. However, the mechanisms of DNA methylation underpinning the adaption of lotus ( Nelumbo nucifera ) ecotypes to high and low latitudes remain unsolved, especially adaptive evolution of their storage organs. Tropical and temperate lotus ecotypes have thin and enlarged rhizomes which are adapted to low and high latitudes, respectively. Here, we investigated the DNA methylomes and transcriptomes of rhizomes of the temperate and tropical lotus to address this issue. Compared with that of the tropical lotus, the DNA of the temperate lotus was significantly more hypermethylated, indicating an increase in global DNA methylation in the lotus, with rhizome enlargement. Meanwhile, genes associated with differentially methylated regions in their promoters tended to be differentially expressed between the two ecotypes. Interestingly, the genes with their expression negatively correlated with methylation levels in their promoters and genomic regions displayed significantly higher transposon coverage, while the genes showing a significant positive correlation between expression and methylation showed lesser transposon coverage. Further, we identified that DNA methylation, especially in the promoter region, was significantly correlated with the expression of many starch‐biosynthetic, gibberellin‐, and brassinosteroid‐signalling genes associated with rhizome differentiation. Overall, our study unveiled that distinct global and local methylation patterns between the two lotus ecotypes contribute to their expression differences and adaptive phenotypic divergence of their storage organs, highlighting the role of DNA methylation in shaping the ecotypic differentiation of lotus.

Design, synthesis and biological evaluation of Schiff’s base derivatives as multifunctional agents for the treatment of Alzheimer’s disease - Jian Shi; Yi Zhou; Keren Wang; Qinge Ma; Rongrui Wei; Qingfeng Li; Yiyang Zhao; Zhanpin Qiao; Shuang Liu; Yumin Leng; Wenmin Liu; Zhipei Sang (Medicinal Chemistry Research, 2021)

Correction to: MiR-96 promotes apoptosis of nucleus pulpous cells by targeting FRS2 - Xiaoxia Yang; Hengping Liu; Qingfeng Zhang; Kan Liu; Dong Yu; Yi Zhang; Zongting Shi (Human Cell, 2020)

MiR-96 promotes apoptosis of nucleus pulpous cells by targeting FRS2 - Xiaoxia Yang; Hengping Liu; Qingfeng Zhang; Kan Liu; Dong Yu; Yi Zhang; Zongting Shi (Human Cell, 2020)

The chimeric genes in the hybrid lineage of Carassius auratus cuvieri (♀)×Carassius auratus red var. (♂) - Qingfeng Liu; Yanhua Qi; Qiuli Liang; Xiujuan Xu; Fangzhou Hu; Jing Wang; Jun Xiao; Shi Wang; Wuhui Li; Min Tao; Qinbo Qin; Rurong Zhao; et al. (Science China Life Sciences, 2018)

Delivery of Helicobacter pylori HpaA to gastrointestinal mucosal immune sites using Lactococcus lactis and its immune efficacy in mice - Rongguang Zhang; Chen Wang; Wenbin Cheng; Guangcai Duan; Qingfeng Shi; Shuaiyin Chen; Qingtang Fan (Biotechnology Letters, 2018)

Heme oxygenase-1 protects spinal cord neurons from hydrogen peroxide-induced apoptosis via suppression of Cdc42/MLK3/MKK7/JNK3 signaling - Siyuan Wang; Tao Zhang; Zhen Yang; Jianhua Lin; Bin Cai; Qingfeng Ke; Wenbin Lan; Jinxing Shi; Shiqiang Wu; Wenping Lin (Apoptosis, 2017)

An engineered Lactococcus lactis strain exerts significant immune responses through efficient expression and delivery of Helicobacter pylori Lpp20 antigen - Rongguang Zhang; Xiaoyan Peng; Guangcai Duan; Qingfeng Shi; Shuaiyin Chen; Chen Wang; Qingtang Fan; Yuanlin Xi (Biotechnology Letters, 2016)

Construction of a recombinant Lactococcus lactis strain expressing a fusion protein of Omp22 and HpaA from Helicobacter pylori for oral vaccine development - Rongguang Zhang; Guangcai Duan; Qingfeng Shi; Shuaiyin Chen; Qingtang Fan; Nan Sun; Yuanlin Xi (Biotechnology Letters, 2016)

The Expression Patterns of Septin-9 After Traumatic Brain Injury in Rat Brain - Hui Mao; Jiao Liu; Wei Shi; Qingfeng Huang; Xide Xu; Lanchun Ni; Feihui Zou; Jinlong Shi; Debao Li; Yonghua Liu; Jian Chen (Journal of Molecular Neuroscience, 2013)

Matrix porosity calculation in volcanic and dolomite reservoirs and its application - Ning Li; Hongliang Wu; Qingfu Feng; Kewen Wang; Yujiang Shi; Qingfeng Li; Xinping Luo (Applied Geophysics, 2009)